A structured model for immune exposures. (11th April 2020) - Vita, Randi; Overton, James A; Dunn, Patrick; Cheung, Kei-Hoi; Kleinstein, Steven H; Sette, Alessandro; Peters, Bjoern
Abstract: An Immune Exposure is the process by which components of the immune system first encounter a potential trigger. The ability to describe consistently the details of the Immune Exposure process was needed for data resources responsible for housing scientific data related to the immune response. This need was met through the development of a structured model for Immune Exposures. This model was created during curation of the immunology literature, resulting in a robust model capable of meeting the requirements of such data. We present this model with the hope that overlapping projects will adopt and or contribute to this work.